Проблема підготовки майбутнього вчителя до використання хмарних технологій у науковому дискурсі - Сегелин Олег; Segelin Oleg (Видавництво «Код», 2025)
Резюме. У статті проаналізовано науковий дискурс проблеми підготовки майбутнього вчителя до використання хмарних технологій. Актуалізовано необхідність побудови єдиного інформаційного простору в освіті через використання хмарних технологій. Особливу увагу зосереджено на студіюванні питань підготовки майбутнього вчителя інформатики до використання хмарних технологій у професійній діяльності. Узагальнено, що підготовка майбутніх учителів до використання хмарних технологій є критично важливою проблемою для сучасної освіти як складний науковий виклик, який потребує комплексного підходу, враховуючи теоретичні, методичні, психологічні та соціальні аспекти.

Abstract. The article analyzes the scientific discourse of the problem of preparation of the future teacher for the use of cloud technologies. The need to build a single information space in education through the use of cloud technologies is updated. The phenomenon of «preparation» as a key concept of research is specified. The analysis of scientific sources showed the diverse of the author’s positions on the interpretation of the concept of «preparation» in the plane of problems raised by scientists. In scientific research, the concept of «preparation» is characterized as the formation of knowledge, skills, competences and qualities of the individual necessary to solve certain tasks of professional activity. The multi-vector of definition of the concept of «professional training» in scientific works is presented. In the field of scientific studies of the raised problem, work is presented, which highlights the main possibilities and advantages of the use of cloud technologies in the process of preparation of the future teacher, focuses on the use of cloud technologies in the professional training of teachers of different specialties. Particular attention is focused on the studies of the preparation of the future computer science teacher for the use of cloud technologies in professional activity. It is noted that the professional training of the future teacher for the use of cloud technologies involves the formation of knowledge, skills and skills necessary for the effective use of cloud services in future pedagogical activity. This includes an understanding of the principles of cloud technologies, the ability to use different cloud services for storage and exchange of educational materials, organization of joint work with students and colleagues, as well as to create an interactive cloudy-oriented educational environment. It is generalized that the preparation of future teachers for the use of cloud technologies is a critical problem for modern education as a complex scientific challenge that requires a comprehensive approach, taking into account theoretical, methodological, psychological and social aspects.
The problem of preparing a future teacher for the use of cloud technologies in scientific discourse
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: використання; інформатика; майбутній учитель; підготовка; професійна підготовка; хмарні сервіси